2013
DOI: 10.2225/vol16-issue6-fulltext-17
|View full text |Cite
|
Sign up to set email alerts
|

Influence of novel lignocellulosic residues in a biobed biopurification system on the degradation of pesticides applied in repeatedly high doses

Abstract: Background:The biobed is a simple biopurification system used to prevent the point-source pesticide contamination that occurs at farm level. The typical composition of the biomixture used in this system is soil, peat and straw in volumetric proportions of 1:1:2. The principal component is straw due to its positive effects on biological activity and thus pesticide degradation. However, access to straw can be limited in some regions, so it must be replaced by other more readily available lignocellulosic residues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Although some BPS achieves high pesticide removal efficiencies, the degradation rate of pesticides and their metabolites that are very persistent or mobile is low (Diez et al . ; Urrutia et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Although some BPS achieves high pesticide removal efficiencies, the degradation rate of pesticides and their metabolites that are very persistent or mobile is low (Diez et al . ; Urrutia et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the authors reported that straw can be partially or totally replaced by oat husk, thereby permitting an effi cient degradation of pesticide mixture, and that straw can be only partially replaced by barley husk and sawdust in the biomixture to allow effi cient pesticide degradation. Recently, Diez et al ( 2013b ) assessed two alternate lignocellulosic materials (barley husks and pine sawdust) as partial substitutes for straw in a biomixture on the degradation of a repeatedly applied mixture of six pesticides (atrazine, isoproturon, iprodione, chlorpyrifos, diazinon, and carbendazim). The results showed that the highest degradation effi ciency was found in mixtures containing straw and barley husks.…”
Section: Pesticide Degradation In Biobeds: Studies At Laboratory Scalementioning
confidence: 99%
“…To meet European environmental quality standards in the field of water policy [2], efforts must be made to prevent groundwater contamination. A possible strategy to reduce the risk of point source contamination by pesticides is to use organic matter as a soil amendment in agricultural practices [3][4][5][6][7][8][9] or to use it in on-farm biopurification systems, commonly referred to as a "biobed" [4,10]. These methods, compared to several techniques used for pesticide removal (e.g., sorption on activated carbon, oxidation with ozone, photocatalytic degradation, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Olive oil solid waste is free of heavy metals and pathogenic microorganisms, and its application significantly increases soil aggregate stability, having great potential for improving the soil structure of coarse-textured soil in the short-or long-term, and increasing the concentrations of nutrients and organic matter, phenolic compounds and total microbial count, so its addition to agricultural soils has been proposed as a solution for its disposal [22][23][24]. The use of wood residues as low-cost adsorbents has been proposed for the immobilization of pesticides in soil and biobeds [4,10]. Using wood residues improves soil properties, such as soil water content and water use efficiency, decreases the bulk density of the soil amended while soil aggregates increase, reduces runoff during heavy rainfall, and increases nitrogen uptake and the crop yield of barley [20].…”
Section: Introductionmentioning
confidence: 99%